Tafsir Ayat-Ayat Keluarga: Mengkaji Posisi Wanita Dalam Struktur Sosial Islam - Muhammad Taufiq Hidayat; Zainal Arifin Zakaria; Sugeng Wanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study examines the position of women in the Islamic social structure through the interpretation of the verses of the Qur'an related to the family, a rich and complex topic covering domestic roles to public participation. The main focus is the interpretation of Surah An-Nisa' verse 34 regarding men as “qawwam” (leaders or those responsible) for women. This study uses a qualitative method with a literature study approach, collecting data from books, journals, and other relevant documents. This study shows that scholars such as Al-Thabari, Al-Qurthubi, Ibn Kathir, Fakhruddin Al-Razi, and Al-Baghawi explain that “qawwam” refers to the responsibility of men to protect and provide for the family, not absolute superiority or the revocation of women's rights. Steps to deal with “nusyuz” (disobedience) of wives, such as advice, separation from bed, and light beatings, must be carried out gradually, without excessive violence, and as a last resort to maintain household harmony. Overall, the interpretation of the verses of the Qur'an shows that Islam places women in a noble position with balanced rights and responsibilities, covering the domestic and public spheres, which requires a comprehensive and contextual understanding so that Islamic values ​​remain relevant and answer contemporary challenges. The novelty of this research lies in emphasizing the balance of the role of “qawwam” as a leadership responsibility rather than absolute superiority, as well as the dynamic public participation of women.